Increased prevalence of poor sulphoxidation in patients with rheumatoid arthritis: effect of changes in the acute phase response and second line drug treatment. Issue 3 (March 1992) - Emery, P; Bradley, H; Gough, A; Arthur, V; Jubb, R; Waring, R
Abstract : A minority of normal subjects have an impaired ability to oxidise sulphur, which is associated with an increased risk of side effects when they receive sulphur containing drugs. In 114 patients with rheumatoid arthritis a greatly increased prevalence of poor sulphoxidation was found in 82 (72%) patients compared with 70/200 (35%) healthy controls, 45/121 (37%) controls matched for age, and 4/35 (11%) of the normal aged general population. In a longitudinal study of 37 patients there was no significant alteration in sulphoxidation status after the introduction of a second line drug or with marked changes in the acute phase response. It seems, therefore, that the poor sulphoxidation status in patients with RA is not an epiphenomenon and may be an important factor in determining the clinical features of rheumatoid disease.